REGIONAL AND DYNAMIC ANALYSIS OF HEALTHCARE SECTOR SUSTAINABILITY (Marketing Journal, 2026)
In this article, the development dynamics and sustainability of the service sector, including healthcare services, across regions are analyzed. The study is conducted based on monthly growth rates of market services and annual growth indicators of healthca re services. Using official statistical data, short -term and long -term development trends of the service sector are assessed. The results indicate that the № 1 -SON YANVA R, 202 6-YIL 230 service sector is characterized by a high level of adaptability to economic fluctuations, while a stable growth trend in healthcare services is maintained across regions. The obtained findings substantiate the socio -economic significance of the service sec tor, particularly healthcare services, and may be applied in improving regional development policies.
Keywords: service sector; healthcare services; regional development; sustainability; growth dynamics; statistical analysis